Honne and Tatemae: A Survey on The Teaching of Cross-Cultural Communication at LPK Sumatra & Java - Rasiban, Linna Meilia; Hardianti, Novi (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2022)
In preparing the life of interns to work in Japan, it is important to teach Japanese culture, especially how to communicate in the cross-cultural context that applies in Japan. Therefore, this study aims to find out the application of Nihonjijo learning at the Work Training Institute (LPK), especially cross-cultural communication about tatemae. Focus on observing the application of tatemae culture only in the West Sumatra and Java Work Training Institute. The research method used is a quantitative descriptive analysis technique. The research instrument used in this study was a picket or questionnaire. The study participants were teachers who taught at the West Sumatra and Java area Job Training Institute. The sample was 9 person of teachers who taught and worked with Japanese people or still work with Japanese. The results show that 1) Almost all LPKs teach nihonjijo in preparation for internship in Japan, 2) A small number of them teach tatemae and honne topics in the study of nihonjijo/ ibunkarikai 3) Observed from the experiences experienced by teachers, most teachers when work and life in Japan they met the tatemae culture more often rather than honne, 4) Some teachers hesitate to distinguish whether he experiences a tatemae or a honne. Because these reasons, that’s why it is important to conduct further research, and to understand better about the Japanese communication culture very well.